The Emerging Application of Itaconate: Promising Molecular Targets and Therapeutic Opportunities - Lin, Jiaqi; Ren, Jinxuan; Gao, Dave Schwinn; Dai, Yi; Yu, Lina (Frontiers in Chemistry, 2021)
Metabolites have recently been found to be involved in significant biological regulation and changes. Itaconate, an important intermediate metabolite isolated from the tricarboxylic acid cycle, is derived from cis-aconitate decarboxylation mediated by immune response gene 1 in mitochondrial matrix. Itaconate has emerged as a key autocrine regulatory component involved in the development and progression of inflammation and immunity. It could directly modify cysteine sites on functional substrate proteins which related to inflammasome, signal transduction, transcription, and cell death. Itaconate can be a connector among immunity, metabolism, and inflammation, which is of great significance for further understanding the mechanism of cellular immune metabolism. And it could be the potential choice for the treatment of inflammation and immune-related diseases. This study is a systematic review of the potential mechanisms of metabolite associated with different pathology conditions. We briefly summarize the structural characteristics and classical pathways of itaconate and its derivatives, with special emphasis on its promising role in future clinical application, in order to provide theoretical basis for future research and treatment intervention.